Voksne etniske minoritetsmænd - marginalisering og intersektionalitet - Jensen, Sune Qvotrup; Larsen, Jeppe Fuglsang; Christensen, Ann-Dorte (Kvinder, Køn & Forskning, 2018)
Adult Ethnic Minority Men - Marginalization and Intersectionality Adult ethnic minority men make up a blind spot in gender and masculinity research. The article contributes to Danish gender studies by examining adult ethnic minority men in a suburb of Aalborg. The analysis applies an intersectional perspective as well as conceptualizations of class travel and othering. Methodologically it is based on qualitative interviews with 24 ethnic minority men living in the area. The article analyzes specific processes of marginalization in relation to local culture and social politics; implications of downward class journey; and processes of othering. One of the main findings is that the marginalized position of these adult ethnic men is related to intersecting categories where for instance the downward class journey and the processes of othering are intertwined and inseparable.